Protocol and statistical analysis plan for the PREventing cardiovascular collaPse with Administration of fluid REsuscitation during Induction and Intubation (PREPARE II) randomised clinical trial. Issue 9 (18th September 2020) - Russell, Derek W; Casey, Jonathan D; Gibbs, Kevin W; Dargin, James M; Vonderhaar, Derek J; Joffe, A M; Ghamande, Shekhar; Khan, Akram; Dutta, Simanta; Landsperger, Janna S; Robison, Sarah W; Bentov, Itay; et al.
Abstract : Introduction: Cardiovascular collapse is a common complication during tracheal intubation of critically ill adults. Whether administration of an intravenous fluid bolus prevents cardiovascular collapse during tracheal intubation remains uncertain. A prior randomised trial found fluid bolus administration to be ineffective overall but suggested potential benefit for patients receiving positive pressure ventilation during tracheal intubation. Methods and analysis: The PREventing cardiovascular collaPse with Administration of fluid REsuscitation during Induction and Intubation (PREPARE II) trial is a prospective, multi-centre, non-blinded randomised trial being conducted in 13 academic intensive care units in the USA. The trial will randomise 1065 critically ill adults undergoing tracheal intubation with planned use of positive pressure ventilation (non-invasive ventilation or bag-mask ventilation) between induction and laryngoscopy to receive 500 mL of intravenous crystalloid or no intravenous fluid bolus. The primary outcome is cardiovascular collapse, defined as any of: systolic blood pressure <65 mm Hg, new or increased vasopressor administration between induction and 2 min after intubation, or cardiac arrest or death between induction and 1 hour after intubation. The primary analysis will be an unadjusted, intention-to-treat comparison of the primary outcome between patients randomised to fluid bolus administration and patients randomised to no fluid bolus administration using a χ 2 test. The sole secondary outcome is 28-day in-hospital mortality. Enrolment began on 1 February 2019 and is expected to conclude in June 2020. Ethics and dissemination: The trial was approved by either the central institutional review board at Vanderbilt University Medical Center or the local institutional review board at each trial site. Results will be submitted for publication in a peer-reviewed journal and presented at scientific conferences. Trial registration number: NCT03787732 .